Use of motion capture-coupled ultrasound sensors to determine scapular position. Issue 6 (2nd November 2021) - Vicini, Anthony; Sabick, Michelle
ABSTRACT: Ultrasonic imaging is a safe, established, and non-invasive method to visualise the locations of structures within the body. Coupling existing skin mounted motion capture markers to ultrasound sensors could allow for precise measurement of positions and orientations of bones hidden under the skin, mitigating the effects of relative displacement between skin and bone that occurs in standard motion capture techniques. This is especially important in motions where skin-mounted markers are inaccurate, such as when tracking scapular position while shoulder abduction is greater than 80 degrees. Previous in silico research has shown that five ultrasound-coupled motion capture clusters could provide sub-millimetre levels of scapular RMS error. This study builds upon those results. The position of a scapular phantom measured by the motion capture plus ultrasound (MC+U) technique was compared to the phantom position as quantified by CT. The root mean squared measurement error in overall scapular position was 2.28 ± 0.56 m m . Mean translational and rotational errors were 0.74 mm and 0.42°, respectively. This level of accuracy would make MC+U a valuable new tool for quantifying scapular position and motion in vivo . The results of this study confirm that the further development of the MC+U technique is warranted and establish a reasonable target for the accuracy of this technique for future in vivo studies.